Validation and Characterization of Platelet-Rich Plasma in the Feline: A Prospective Analysis - Chun, Nicole; Canapp, Sherman; Carr, Brittany Jean; Wong, Valerie; Curry, Jeff (Frontiers in Veterinary Science, 2020)
Objective: To quantitate key parameters of the platelet-rich plasma (PRP) product from a commercially available system¹ in healthy, adult felines. Materials and methods: A prospective study was performed from January 2019 to April 2019. 11 adult, healthy cats were used to prospectively analyze a commercially available PRP system¹. A whole blood sample and a PRP sample that was processed immediately following blood draw according to the manufacturer’s protocol were collected from each cat. The mean whole blood and PRP product platelet, RBC, WBC, neutrophil, monocyte, and lymphocyte concentrations were determined. The mean PRP product values were compared to the mean whole blood baseline values using a paired t-test with significance established at p = 0.05. Results: Mean platelet concentration was significantly increased (p = 0.0155). Mean RBC concentration was significantly decreased (p <0.0001). Mean neutrophil concentration was significantly decreased (p <0.0001). There was no statistically significant difference in mean WBC, monocyte, and lymphocyte concentrations. Clinical Relevance: The analyzed PRP system increased platelet concentration, while significantly reducing the RBC and neutrophil concentrations. Further study is warranted to determine the clinical applications and efficacy of PRP in felines, and the ideal concentrations of and relationships between platelets, red blood cells, and leukocytes needed for therapeutic effect.